Functional Study of BpPP2C1 Revealed Its Role in Salt Stress in Betula platyphylla - Xing, Baoyue; Gu, Chenrui; Zhang, Tianxu; Zhang, Qingzhu; Yu, Qibin; Jiang, Jing; Liu, Guifeng (Frontiers in Plant Science, 2021)
PP2C protein phosphatase family is one of the largest gene families in the plant genome. Many PP2C family members are involved in the regulation of abiotic stress. We found that BpPP2C1 gene has highly up-regulated in root under salt stress in Betula platyphylla. Thus, transgenic plants of Betula platyphylla with overexpression and knockout of BpPP2C1 gene were generated using a zygote transformation system. Under NaCl stress treatment, we measured the phenotypic traits of transgenic plants, chlorophyll-fluorescence parameters, peroxidase (POD) activity, superoxide dismutase (SOD) activity, and malondialdehyde (MDA) content. We found that BpPP2C1 overexpressed lines showed obvious salt tolerance, while BpPP2C1 knocked out plants were sensitive to salt stress. Transcriptome analysis identified significantly amount of differentially expressed genes associated with salt stress in BpPP2C1 transgenic lines, especially genes in abscisic acid signaling pathway, flavonoid biosynthetic pathway, oxidative stress and anion transport. Functional study of BpPP2C1 in Betula platyphylla revealed its role in salt stress.